Emergence of decreased susceptibility and resistance to extended-spectrum cephalosporins in Neisseria gonorrhoeae in Korea - Lee, Hyukmin (J Antimicrob Chemother, 2015)
OBJECTIVES: Antimicrobial resistance (AMR) in Neisseria gonorrhoeae is a major concern globally; however, no comprehensive AMR data for gonococcal isolates cultured after 2006 in Korea have been published internationally. We determined the susceptibility of N. gonorrhoeae isolates cultured in 2011–13, the mechanism of extended-spectrum cephalosporin (ESC) resistance and the molecular epidemiology of gonococcal strains in Korea. METHODS: In 2011–13, 210 gonococcal isolates were collected in Korea and their AMR profiles were examined by the agar dilution method. The penA, mtrR, penB, ponA and pilQ genes were sequenced in 25 isolates that were resistant to ESCs and 70 randomly selected isolates stratified by year. For molecular epidemiology, N. gonorrhoeae multiantigen sequence typing and MLST were performed. RESULTS: None of the N. gonorrhoeae isolates was susceptible to penicillin G and most were resistant to tetracycline (50%) and ciprofloxacin (97%). The rates of resistance to ceftriaxone, azithromycin, cefpodoxime and cefixime were 3%, 5%, 8% and 9%, respectively. However, all isolates were susceptible to spectinomycin. Twenty-one (84%) of the 25 ESC-resistant isolates contained the non-mosaic PBP2 XIII allele; however, the remaining 4 (16%) possessed the mosaic PBP2 X allele, which has been previously associated with ESC resistance including treatment failures. CONCLUSIONS: In Korea, susceptibility to spectinomycin remains high. However, the recent emergence of ESC-resistant N. gonorrhoeae strains, including strains possessing the PBP2 mosaic X and non-mosaic XIII alleles, is a major concern and enhanced AMR surveillance is necessary to prevent transmission of these strains.